2018
DOI: 10.1038/s41598-018-30167-5
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-impedimetric Biosensor for Onsite Monitoring of Ascospores and Forecasting of Sclerotinia Stem Rot of Canola

Abstract: Sclerotinia stem rot, caused by the fungal pathogen Sclerotinia sclerotiorum, is a destructive disease of canola and many other broadleaf crops. The primary inoculum responsible for initiating Sclerotinia epidemics is airborne ascospores released from the apothecia of sclerotia. Timely detection of the presence of airborne ascospores can serve as an early-warning system for forecasting and management of the disease. A major challenge is to develop a portable and automated device which can be deployed onsite to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…Although PCR can achieve the detection of a few nanograms of S. sclerotiorum DNA, its complex operation and instrumentation hinder their potential application in the field . Our proposed method is simple, portable, and sensitive to single spores, which can allow us to provide an accurate and early warning system to avoid SSR outbreaks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PCR can achieve the detection of a few nanograms of S. sclerotiorum DNA, its complex operation and instrumentation hinder their potential application in the field . Our proposed method is simple, portable, and sensitive to single spores, which can allow us to provide an accurate and early warning system to avoid SSR outbreaks.…”
Section: Resultsmentioning
confidence: 99%
“…Nano- and micromachined devices emerge as an alternative to provide such a platform. 20 , 24 In this study, we designed a microfluidic device based on a nanoelectrode-activated microwell array for the capture and quantification of S. sclerotiorum spores. Microwell arrays have been commonly used for high-throughput cell sequencing 25 29 and cell pairing, 30 , 31 as well as for cancer cell identification and characterization.…”
Section: Introductionmentioning
confidence: 99%
“…EIS’s working principle is based on the measure of the opposition to the flow of the current that results from redox reactions and molecular interactions at the electrode surface when voltage is applied to the cell membrane ( Shoute et al, 2018 ). Khater et al recently developed a labelless impedimetric biosensor for the detect the nucleic acid of citrus tristeza virus and the experiment demonstrated that this method of a high potential can be used in fields to detect plant pathogens.…”
Section: Biosensor Technologies For Plant Pathogen Detectionmentioning
confidence: 99%
“…As previously mentioned, conventional laboratory techniques have the sensitivity and specificity for the detection of microbial pathogens in water. However, due to lack of rapid analysis, overall cost, and experimental complexity they are unsuitable for the purpose of on-site detection [113]. Nonetheless, the development of truly portable and autonomous diagnostic devices remains a major task.…”
Section: How To Detect On-sitementioning
confidence: 99%